PERBANDINGAN SONETA ARTIFISIAL WING KARDJO DENGAN SONETA SITOR SITUMORANG (THE COMPARISON OF WING KARDJO’S ARTIFICIAL SONNET WITH SITOR SITUMORANG’S) - Suyatno, Suyono (METASASTRA: Jurnal Penelitian Sastra, 2013)
Soneta di tangan dua penyair yang berbeda melahirkan kecenderungan yang berbeda pula. Soneta Sitor Situmorang cenderung lebih liris dan ekspresi estetiknya pun lebih setia pada konvensi soneta. Sementara itu, soneta Wing Kardjo cenderung naratif dan hanya memanfaatkan pola ekspresi soneta sambil memarodikannya. Kecenderungan memarodikan soneta bagi Wing Kardjo sejalan dengan keinginannya memarodikan situasi sosial politik di negeri ini. Kecenderungan liris pada soneta Sitor Situmorang tidak terlepas dari muatan soneta Sitor yang menampilkan persoalan-persoalan personal, terutama dalam hal relasi lelaki-perempuan. Di sisi lain, kecenderungan naratif soneta Wing Kardjo terkait dengan muatan soneta Wing Kardjo yang merupakan respon terhadap situasi sosial politik di negeri ini.Abstract:Sonnets in the hands of two different poets creat different tendencies. Sitor Situmorang’s sonnet tends to be more lyrical and aesthetic in its expression. It  is more faithful to those stated in the convention. Meanwhile, Wing Kardjo’s  tends to be  narrative and only make use of the expres- sion pattern of the sonnet while parodying it. Tendency of parodying  sonnet for  Wing Kardjo was in line with his desire for parodying social and political situation in the country. Lyrical tendencies in the  Sitor Situmoran’s sonnet cannot be separated from the type of  his work  depicting personal problems, especially, in the male-female relationships. On the other hand, the tendency of the Wing Kardjo ‘s  narrative sonnet is the content of  Wing Kardjo’s that   was a response to the social and political situation in the country.